Phenoloxidase -activity in different tropical prawns and its sensitivity to sulphiting agents - Chakrabarti, R (Indian Journal of Fisheries, 2011)
Presence and characteristics of phenoloxidase in Indian prawn were reported by Antony et al. (1968, 1975) and Savagaon et al. (1978). They also tried to find out probable factors responsible for melanosis. They reported high order of phenoloxidase activity in head juice and tail extract of Indian prawn. Sovagaon et al. (1978) reported the existence of zymogen form of phenoloxidase in penaeid prawn and gave possible mechanism of activation by endogenous proteolytic enzymes. The polyphenolase reactions are accelerated by copper and other metallic ions (Fieger et al. 1961). Antony et al. (1968) reported that pH of tissue, exposure to higher temperature up to 55Â°C and access to oxygen are important factors for black spot formation.